2015
DOI: 10.1080/21551197.2015.1054575
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Health Outcomes Among Older Adults: The Role of Cost-Related Medication Underuse

Abstract: The purpose of this study is to examine the relationship between food security and cost-related medication underuse among older adults (persons aged 65 years and older) in the United States; and to determine if this relationship differs by sex, chronic disease status, and type of health insurance. Data are from a combined sample of older adults in the 2011 and 2012 National Health Interview Survey (N = 10,401). Both bivariate and multivariate analyses show a dose-response relationship between food insecurity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 36 publications
6
64
0
Order By: Relevance
“…Despite the removal of adolescents and 2 provinces from our sample, the prevalence of cost-related nonadherence to prescription drugs was virtually the same as that reported by Law and colleagues 5 using the same data. Similar to findings from US-based studies, 16,21,22 after adjustment for confounders, we for respondents with and without prescription drug insurance by household food insecurity status; 332 respondents with missing insurance status were excluded from the analysis. Poisson regression with bootstrapped standard error was used, adjusting for household income, imputed income, income source, sex, age, Aboriginal status, housing tenure, household type, province of residence and number of different drugs prescribed.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the removal of adolescents and 2 provinces from our sample, the prevalence of cost-related nonadherence to prescription drugs was virtually the same as that reported by Law and colleagues 5 using the same data. Similar to findings from US-based studies, 16,21,22 after adjustment for confounders, we for respondents with and without prescription drug insurance by household food insecurity status; 332 respondents with missing insurance status were excluded from the analysis. Poisson regression with bootstrapped standard error was used, adjusting for household income, imputed income, income source, sex, age, Aboriginal status, housing tenure, household type, province of residence and number of different drugs prescribed.…”
Section: Discussionmentioning
confidence: 98%
“…A growing literature has established robust relationships between food insecurity and worse health. Food insecure households have difficulty meeting basic needs such as refilling medical prescriptions ( Afulani, Herman, Coleman-Jensen, & Harrison, 2015 ) and providing adequate nutrition ( Duffy, Zizza, Jacoby, & Tayie, 2009 ). Food insecurity is associated with poorer self-rated mental and physical health among adults ( Alaimo, 2005 ; Stuff et al, 2004 , Stuff et al, 2004 ) and food insecure households with children have higher risk of iron deficiency and poorer dental outcomes ( Chi et al, 2014 , Skalicky et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,5,[27][28][29] For example, using the National Health Interview Survey (NHIS), Berkowitz et al 27 estimated that approximately one in three chronically ill NHIS participants are unable to afford food, medications, or both. Bromley et al 28 reported that financial obstacles, lack of insurance, decreased access to care, and intermittent primary care visits are associated with a lower likelihood of undergoing colorectal cancer screening in an at-risk African American population.…”
Section: Barriersmentioning
confidence: 99%
“…[1][2][3][4][5] There are serious and alarming consequences of the underuse of health care. For example, Farley and his colleagues 3 estimated that increasing the use of nine clinical prevention services to more optimal levels could prevent 50,000-100,000 deaths each year among adults younger than 80 years of age.…”
Section: Introductionmentioning
confidence: 99%